Characterising techniques and marine resource exploitation for Iron Age and Late Islamic lime production on Jubail Island (Abu Dhabi) : the 2021 archaeological investigations - Lambert, Aurore; Biets, Corentin; Durand, Benjamin; Casado, Célia; Lassalle, Élodie; Lorente-Sebastián, Paloma; Peres, Thibaut; Veron, Jan; Broglia de Moura, Samara; Beech, Mark Jonathan; Cuttler, Richard Thorburn Howard; Magee, Peter (Proceedings of the Seminar for Arabian Studies, 2023)
As part of Jubail Island’s development process, an archaeological intervention was undertaken by Eveha International in 2021, monitored by the Historic Environment Department at the Department of Culture and Tourism (DCT), Abu Dhabi. The scientific goals were to identify and characterise the archaeological settlements on Jubail Island and to define the site’s environmental context. Both Iron Age and late Islamic lime production were discovered through heap-burning kilns and constructed kilns, using coral and shells as raw material. The island was used for lime production over a long time period. No permanent settlements have been identified to date and artefacts are few. The production seems to be opportunistic and intermittent in scale. Further research is needed to relate the late Islamic period production to the lifestyle shift of the nomadic population as they shed light on an unsuspected and underrated kind of lime production. That is part of a much larger occupation of the island and of the intricate socio-cultural history of Abu Dhabi’s development. Considering the surrounding surveys and Abu Dhabi historical development, it merits further investigation and promotion to the general public.